Synergistic effects of yeast and plant growth-promoting bacteria on Tobacco growth and soil-borne disease suppression: evidence from pot and field experiments - Teng, Kai; Zhou, Yu; Mao, Hui; Long, Xianjun; Zhang, Sheng; Ma, Jingjing; Meng, Delong; Yin, Huaqun; Xiao, Yunhua (Frontiers in Plant Science, 2024)
Background Tobacco (Nicotiana tabacum L.) is an important economic crop, and the use of plant growth-promoting bacteria (PGPB) to enhance its growth and suppress soil-borne diseases has garnered considerable research interest. However, the potential of yeast to augment the growth-promoting and disease-suppressing effects of PGPB on tobacco remains unclear. Methods This study investigated the effects of Pichia sp. microbial fertilizer (J1), PGPB-Klebsiella oxytoca microbial fertilizer (ZS4), and their composite fertilizer (JZ) on tobacco growth indexes, soil properties, and soil microbial community through a pot experiment. Additionally, field experiments were conducted to further assess the efficacy of the composite microbial fertilizer on tobacco growth and the incidences of soil-borne diseases, including tobacco bacterial wilt (TBW) and tobacco black shank (TBS). Results and discussions In the pot experiment, application of the microbial fertilizers significantly enhanced soil organic matter (OM), total nitrogen (TN), total phosphorus (TP), total potassium (TK), available phosphorus (AP), and available potassium (AK) levels. Compared to the control group (CK), J1, ZS4, and JZ microbial fertilizers significantly promoted tobacco growth, and the composite microbial fertilizers demonstrated superior to the individual microbial fertilizers. We found that the application of microbial fertilizer led to significant alterations in the structure and composition of the bacterial and fungal communities based on the high-throughput sequencing of 16S rRNA and internal transcribed spacer (ITS) regions. The bacterial and fungal diversity indexes showed a decreasing trend. Key microorganisms such as Sphingomonas, Kitasatospora, Nitrosospira, Mortierella, and Trichoderma were identified as influential in regulating soil physicochemical parameters to enhance tobacco growth. Functional prediction further demonstrated a significant increase in the relative abundances of certain enzymes, including Alkaline phosphatase, 1-aminocyclopropane-1-carboxylate deaminase (ACC deaminase), and Peroxidase, as well as antimicrobial substances like Tetracycline, Isoquinoline alkaloid, and Phenylpropanoids, following inoculation with the fertilizer. Besides, field experiments revealed that the JZ fertilizer significantly promoted tobacco growth and reduced the incidence of TBW and TBS, indicating its potential for further application in tobacco cultivation.